Cell Transformation and the Evolution of a Field of Precancerization As It Relates to Oral Leukoplakia - L. Feller; J. Lemmer (International Journal of Dentistry)
Potentially malignant oral leukoplakias arise within precancerized epithelial fields consisting of cytogenetically altered keratinocytes at various stages of transformation. The evolution of a clone of keratinocytes culminating in a precancerous phenotype is a function of the number of mutagenic events, rather than the sequential order in which they occur. The altered molecular configurations of the transformed precancerous keratinocytes may confer upon them a growth advantage in relation to the unaltered neighbouring keratinocytes. Replicative clonal expansion of these keratinocytes results in the progressive replacement of the surrounding normal keratinocytes by the fitter clone or clones of altered cells. The precancerized oral epithelial field may have a clinically normal appearance and microscopically may be normal or may show dysplasia. Oral leukoplakias arising within a precancerized epithelial field in which the keratinocytes show DNA aneuploidy or loss of heterozygosity at certain specific chromosomal loci have the potential to progress to carcinoma. The pathogenic mechanisms that drive the carcinomatous transformation of oral leukoplakias, in which cytogenetic alterations in the keratinocytes cannot be detected, are unknown.